Linking urban transport and land use in developing countries - Robert B Cervero (Journal of Transport and Land Use)
The mobility challenges of the developing world are considerably different than those in wealthier, advanced countries, and so are the challenges of coordinating transportation and land use. Rapid population growth, poverty and income disparities, overcrowded urban cores, poorly designed road networks, spatial mismatches between housing and jobs, deteriorating environmental conditions, and economic losses from extreme traffic by congestion are among the more vexing challenges faced by developing cities that could be assuaged through improved coordination of transportation and urban development. This is underscored by examples reviewed in this paper from South Asia, Southeast Asia, China, India, Africa, and South America. It is concluded that whatever is done to improve transportation and land-use integration must be pro-poor. The cardinal features of integrated and sustainable transport and urbanism everywhere---accessible urban activities and safe, attractive walking and cycling environs---are particularly vital to the welfare and prosperity of urbanites in the world's poorest countries.